A materialistic perspective of consumer decision-making styles. Issue 2 (18th October 2019) - Chaudhary, Sartaj; Dey, Ajoy Kumar
Abstract : Purpose: Materialism has become a topic of increasing interest to researchers and policymakers because it can influence consumer behavior. However, a clear picture of how this phenomenon impacts consumers has proven to be elusive. Using an integrated framework, this paper aims to derive hypotheses from theoretical concepts of materialism and consumer decision-making styles and uses a survey of 1, 216 respondents in India to test the hypotheses. Design/methodology/approach: The present study is the first of its kind to test the impact of materialist values on consumer decision-making styles among a sample of 13-18 years old school children. The constructs are validated through a first- and second-order confirmatory factor analysis and an integrated second-order structural model is developed. Findings: This study finds that materialism is a positive predictor of "recreation/ hedonistic", ; "confused by over-choice"; "brand consciousness"; "perfectionistic high-quality consciousness"; and "habitual brand loyal" style of consumers. Further, materialism has a negative impact on "price value consciousness" of consumers. These findings have important implications for theory and practice. Research limitations/implications: This study is restricted to school children in the National Capital Region and hence cannot be generalized to the whole young population in India. Originality/value: Conceptualizing both materialism and consumer decision-making styles as second-order constructs, this is a maiden study that examines the impact of materialistic values on the consumer decision-making styles of young consumers.